On the Kinetic Theory of Subauroral Arcs. Issue 8 (26th August 2022) - Mishin, Evgeny; Streltsov, Anatoly
Abstract: We report on a novel scenario of subauroral arcs within strong subauroral ion drifts (SAID)‐STEVE and Picket Fence. Their explanation requires a local source of low‐energy, ε  < 18.75 eV, suprathermal electrons, and N2 vibrational and electronic excitation below ∼270 km. We show that the ionospheric feedback instability in strong SAID flows with depleted density troughs generates intense, small‐scale field‐aligned currents and parallel electric fields below the F2 peak. With these fields, we employed a rigorous numerical solution of the Boltzmann kinetic equation for the distribution of ionospheric electrons and determined the power going to excitation and ionization of neutral gas (the energy balance). The obtained suprathermal electron population and energy balance at altitudes of ∼130–140 km are just what is necessary for Picket Fence. Concerning STEVE, the kinetic theory predictions are in a good qualitative agreement with its basic features, such as the enhanced continuum emissions. Besides, the theory predicts that subauroral arcs might have the transient phase with typical aurora‐like emissions that fade out afterward. Plain Language Summary: Subauroral arcs radically different from usual aurora occur inside subauroral flows (SAID) with depleted density and high electron temperature. Their interpretation requires specific local distributions of electrons and vibrationally excited neutrals. In Picket Fence at ∼130–140 km, the electron distribution function (EDF) is enhanced at energies <18.75 eV. The ionospheric feedback instability within SAID generates small‐scale field‐aligned currents and electric fields nonlinearly increasing with the SAID and depletion magnitude. Via the EDF, these fields control the power going to the excitation of neutrals (the energy balance). Because the EDF deviates from a Maxwellian, we use a rigorous solution of the Boltzmann kinetic equation with the modeled fields. The resulting energy balance at ∼130–140 km corresponds to the EDF and excited neutral species required for Picket Fence. The theory predictions qualitatively agree with the STEVE features above 200 km. Besides, inside SAID with deep depletions the EDF contains many ionizing electrons at ∼170–200 km. Additional ionization changes the initial density profile and the instability development will likely be saturated when the generated fields in the whole altitude range reduce below the ionization threshold. In other words, subauroral arcs might have the transient phase with typical aurora‐like emissions that fade out afterward. Key Points: Ionospheric feedback makes strong small‐scale field‐aligned currents and electric fields in fast subauroral flows with low‐density troughs Solving the kinetic equation with these fields gives suprathermal electrons and excited neutrals explaining the subauroral arcs features The developed theory predicts that subauroral arcs might have the transient phase with typical aurora‐like emissions fading afterward